Mutational signature profiling classifies subtypes of clinically different mismatch-repair-deficient tumours with a differential immunogenic response potential - Giner-Calabuig, Mar; De Leon, Seila; Wang, Julian; Fehlmann, Tara D.; Ukaegbu, Chinedu; Gibson, Joanna; Alustiza-Fernandez, Miren; Pico, Maria-Dolores; Alenda, Cristina; Herraiz, Maite; Carrillo-Palau, Marta; Salces, Inmaculada; et al. (British journal of cancer, 2022)
Background Mismatch repair (MMR) deficiency is the hallmark of tumours from Lynch syndrome (LS), sporadic MLH1 hypermethylated and Lynch-like syndrome (LLS), but there is a lack of understanding of the variability in their mutational profiles based on clinical phenotypes. The aim of this study was to perform a molecular characterisation to identify novel features that can impact tumour behaviour and clinical management. Methods We tested 105 MMR-deficient colorectal cancer tumours (25 LS, 35 LLS and 45 sporadic) for global exome microsatellite instability, cancer mutational signatures, mutational spectrum and neoepitope load. Results Fifty-three percent of tumours showed high contribution of MMR-deficient mutational signatures, high level of global exome microsatellite instability, loss of MLH1/PMS2 protein expression and included sporadic tumours. Thirty-one percent of tumours showed weaker features of MMR deficiency, 62% lost MSH2/MSH6 expression and included 60% of LS and 44% of LLS tumours. Remarkably, 9% of all tumours lacked global exome microsatellite instability. Lastly, HLA-B07:02 could be triggering the neoantigen presentation in tumours that show the strongest contribution of MMR-deficient tumours. Conclusions Next-generation sequencing approaches allow for a granular molecular characterisation of MMR-deficient tumours, which can be essential to properly diagnose and treat patients with these tumours in the setting of personalised medicine.